Influence of Service Quality and Price Perception on Purchasing Decisions: A Study on Passengers at Ahmad Yani Port, Ternate - Shafira Jihan Fairuz Mazaya; M Nahar; Makmun Riyanto (Politeknik Negeri Semarang, 2025)
Based on the Theory of Planned Behavior framework, this study aims to analyze the influence of Service Quality and Price Perception on Purchasing Decisions among passengers at Ahmad Yani Port, Ternate, North Maluku. The survey approach used primary data through a structured questionnaire to 100 respondents with direct experience using port services. Sampling was determined using the Slovin formula and purposive criteria to ensure representativeness. The results showed that Service Quality had no significant effect on Purchasing Decisions, while Price Perception had a positive and significant effect. Simultaneously, both variables were able to explain almost 60% of the variation in passenger decisions, with price aspects proving more dominant than service quality in the context of maritime transportation. Perceptions of affordability, fairness, and price competitiveness emerged as the main determinants in influencing consumer choices. This study's contributions are both theoretical and practical. Theoretically, the study enriches the consumer behavior literature by confirming that price considerations can shift the role of service attributes in the context of island transportation. Practically, the results recommend that port managers prioritize transparent, affordable, and competitive tariff strategies, accompanied by improvements in service facilities and staff responsiveness to maintain long-term passenger satisfaction and loyalty